2019
DOI: 10.1371/journal.pone.0213663
|View full text |Cite
|
Sign up to set email alerts
|

Two conformationally distinct α-synuclein oligomers share common epitopes and the ability to impair long-term potentiation

Abstract: Parkinson’s Disease (PD) is a neurodegenerative disease for which there currently is no cure. Aggregation of the pre-synaptic protein α-synuclein (aSN) into oligomers (αSOs) is believed to play a key role in PD pathology, but little is known about αSO formation in vivo and how they induce neurodegeneration. Both the naturally occurring polyunsaturated fatty acid docosahexaenoic acid (DHA) and the lipid peroxidation product 4-hydroxynonenal (HNE), strongly upregulated during ROS conditions, stimulate the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 71 publications
5
40
0
Order By: Relevance
“…D,E). We have previously shown that only a small part of the DHA‐αSOs dissociates back into monomers after αSO purification using SEC , but the absence of staining upon incubation with 2.5 μ m of monomer shows that these dissociated monomers will not interfere with the identification of αSO binding partners. The lack of binding of monomeric αSN is a vindication of our strategy to work with stabilized αSOs in a cellular context to minimize potential dissociation of the oligomeric state.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…D,E). We have previously shown that only a small part of the DHA‐αSOs dissociates back into monomers after αSO purification using SEC , but the absence of staining upon incubation with 2.5 μ m of monomer shows that these dissociated monomers will not interfere with the identification of αSO binding partners. The lack of binding of monomeric αSN is a vindication of our strategy to work with stabilized αSOs in a cellular context to minimize potential dissociation of the oligomeric state.…”
Section: Resultsmentioning
confidence: 97%
“…The experimental set‐up was validated by coupling DHA‐αSOs to the 5G4 antibody, previously shown to bind aggregated αSN and DHA‐αSOs . DHA‐αSOs were labelled with 0.1 or 0.5 m m of sulfo‐LC‐SDA crosslinker and were then crosslinked to the 5G4 antibody using either 15 or 30 min of UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oligomers formed and stabilized by lipid peroxidation products show much the same neuronal binding and toxicity properties as their unmodified counterparts, whereas more radical changes in preparation procedures ( e.g. , use of iron salts, ethanol, and/or different shaking regimes) can have substantial impact on their cellular activity profiles (Van Diggelen et al ),(Danzer et al ; Qin et al ; Ehrnhoefer et al ; Cremades et al ).…”
Section: Oligomer Structure and Shapementioning
confidence: 99%